Reconnecting with Your Passion: An Action Research Study Exploring Humanities and Professional Nursing - Melissa J. Snyder (Adult Education Research Conference, 2012)
The purposes of this study are to examine the process of how nurses engage in a professional development program that draws on reading and creative narrative writing related to their professional values and ideals and to examine the nurses‘ perspectives on how their involvement in the process and program relates to changes in their professional roles.